Fundamentals of translation - Colina, Sonia (Cambridge Univ. Press, 2015)
"This textbook provides a non- technical introduction to the basic and central concepts of translation theory and practice, including translation briefs, parallel texts and textual functions, cohesion and coherence, and old and new information"--